Research on mechanical harvesting of prickly pear for catle feed (Journal of the Professional Association for Cactus Development, 2021)
In 1988 Texas A&I received a grant to develop a biomass combine to harvest woody brush for use as an industrial fuel source. Since then we have adapted a previously proven Texas Tech cutterhead to a hydrostatically powered John Deere forage harvester. This machine has proven quite capable of harvesting 4 to 6 inch diameter mesquite trees, shredding them, and blowing the shredded biomass to a trailer behind the harvester. We felt this machine might prove useful in harvesting prickly pear cactus for cattle feed. Unfortunately this is not a picked up as is the woody brush. While this process might be useful if is desirable to destroy the cactus, this will certainly not harvest the cactus.